2020
DOI: 10.1039/d0ra06254e
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of infusion and health consequences: a comparative study between orthodox and CTC green teas

Abstract: This study compares the effects of two green tea processing techniques, viz. orthodox and CTC (curl, tear and crush) on the quality parameters and sensory profiles under the geographical and climatic conditions of Assam, India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…In continuation of our earlier study on OGT and CGT, here we have reported the contents of non-toxic (Cu, Fe and Zn, also known as micronutrients) and toxic (Cd, Cr, Ni and Pb) elements in green tea and in their infusions. The biochemical quality parameters and sensory characteristics of OGT and CGT had been reported in our recently published work ( Deka et al, 2020 ). Further, estimated daily intake (EDI), HQ and HI were also determined in the present study for health risk assessment upon consumption of green tea.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…In continuation of our earlier study on OGT and CGT, here we have reported the contents of non-toxic (Cu, Fe and Zn, also known as micronutrients) and toxic (Cd, Cr, Ni and Pb) elements in green tea and in their infusions. The biochemical quality parameters and sensory characteristics of OGT and CGT had been reported in our recently published work ( Deka et al, 2020 ). Further, estimated daily intake (EDI), HQ and HI were also determined in the present study for health risk assessment upon consumption of green tea.…”
Section: Introductionmentioning
confidence: 89%
“…Young fresh shoots of cultivars TV1 (TV stands for Tocklai Vegetative), TV9, TV18, TV20, TV22, TV23 and TV25, RR17/144, Happy Valley 39, 482/12 and Ging186 grown in an identical environment and soil nutrient management practice were collected and green tea was processed in both orthodox and CTC mode following the protocol described by Deka et al (2020) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 CTC black tea processing involves ve principal stages comprising withering, rolling, CTC, fermentation and drying. [18][19][20] The quality potential of black tea is also dependent on the plucking of leaves when aroma precursors are developed. 2 Furthermore considerable chemical changes take place at each processing stage.…”
Section: Introductionmentioning
confidence: 99%